PENGELOLAAN PEMANDIAN ALAM BAH DAMANIK BERBASIS KEARIFAN LOKAL - Gianta Anastasya Damanik (Yayasan Literasi Sains Indonesia, 2026)
Bah Damanik Baths is a nature-based tourist attraction, relying on the potential beauty and natural environment, namely springs, forests, and other ecosystems around the area. Bah Damanik Baths was once used as a bathing place for the Damanik Kings and a place for the Maranggir ritual. This study will explain the changes in the management of Bah Damanik Baths based on local wisdom. Qualitative research methods were conducted by conducting interviews with the traditional leader of Sarimatondang Village, Bah Damanik managers, and local communities to obtain collective memories related to Bah Damanik. Then, a literature review was conducted regarding previous research on Simalungun local wisdom. The data were then analyzed chronologically to see changes in management at Bah Damanik. The results of the study include local wisdom such as habonaron do Bona, Marharoan Bolon, and the Maranggir ritual, which play a foundation for maintaining the Bah Damanik environment. Management based on local wisdom is seen in the prohibition of the use of chemical substances such as shampoo and soap in the Bah Damanik pool area and the prohibition of bringing forbidden items such as processed pork and alcoholic beverages. The practices carried out demonstrate the conservation of the sanctity of Bah Damanik.